A Deep Learning-Based Approach for Damage Detection in Cultural Heritage Images and Generating Heat Maps - Ogdu, Cagatay Umut; Yilmazer, Merve; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2024)
Cultural structures may be damaged and damaged over time due to external factors such as natural and social disasters, which may lead to the loss of national assets if cultural assets are not protected. Therefore, the protection of cultural heritage is of great importance not only for today's generations but also for future. In recent years, deep learning and image processing have made great progress and have become very effective for detecting and analyzing patterns. These techniques can also be used to solve complex problems such as damage detection of structures in the field of cultural heritage. Deep learning methods can be used to determine the current status of structures and detect possible damage by working on images obtained from different angles of structures, while also reducing human errors. In this study, as an important step for the protection of cultural heritage, a detection method was developed using deep learning models on damaged and intact cultural heritage building images. The data set used in the study consists of damaged and intact cultural heritage building images. An attempt was made to determine the model that gave the best results by using pre-trained models with the Transfer Learning method. Heat maps were created using the Grad-CAM method to identify damaged areas on the trained models, thus making it possible to more clearly identify the damaged areas in the image. This method can play an important role in preserving cultural heritage. It can be used to detect damaged areas and direct them to repair. © 2024 IEEE.
2nd International Conference on Sustaining Heritage, ICSH 2024 -- 29 September 2024 through 30 September 2024 -- Virtual, Online -- 205033
Keywords: cultural heritage; damage detection; deep learning; heat maps